Treatment with mRNA coding for the necroptosis mediator MLKL induces antitumor immunity directed against neo-epitopes - Lien Van Hoecke (Nature Portfolio, 2018)
Necroptosis has immunogenic cell death properties. Here, the authors show that the intra-tumor delivery of mRNA that codes for the necroptosis effector MLKL triggers neo-epitope-specific anti-tumor T cell responses and inhibits primary tumor growth and lung metastasis.